Al-Ta’bîr al-Siyâsî lî al-Muslîmîn al-Shînîyîn bî Jember fî Mandzûri fiqh al-Siyasah: Aghlabiyah Dîniyah wa Aqalliyah ‘Arâqiyah : - Bahar, Moh. Syaeful; Dodik Harnadi; Ali Rohmad, Ahmad Khubby (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This study examines how Chinese Muslims in Jember, Indonesia, negotiate their unique position as an ethnic minority within a religious majority through the lens of fiqh al-siyasah (Islamic political jurisprudence). Using a qualitative approach that combines in-depth interviews with community leaders, participant observation, and documentary analysis, the research reveals three main patterns of political expression: a response of avoidance justified by the principle of preventing means to ends, an adaptive response rooted in expediency through strategic alignment with the Nahdlatul Ulama and limited individual participation. At the socio-religious level, Chinese Muslims have devised a complex dual-identity strategy that preserves Chinese cultural authenticity and Islamic orthodoxy through the creative application of the principles of custom, the distinction between custom and worship, and the architectural-ritual synthesis embodied in the Muhammad Cheng Ho Mosque. Their positions on contemporary theological-political issues—the Ahok blasphemy case, the call for a caliphate, fundamentalist movements, and Indonesian democracy—demonstrate a sophisticated application of political jurisprudence concepts, including siyasah syar’iyah, maqasid al-sharia, istihsan and istishlah. The study contributes theoretically by expanding fiqh siyasah to include ‘composite minorities’—ethnic minorities within religious majorities—and practically by showing how classical fiqh principles can provide a flexible yet sound framework for Muslim minorities navigating complex pluralistic contexts. The findings confirm that Islamic jurisprudence is inherently dynamic and contextual (rulings change with changing circumstances) and that creative cultural-religious synthesis can achieve social integration without compromising doctrinal fundamentals.